Exponential bipartite tracking consensus in cooperative-antagonistic nonlinear Multi-Agent Systems with multiple communication time-varying delays. (December 2022) - Lui, Dario Giuseppe; Petrillo, Alberto; Santini, Stefania
Abstract: This article deals with the bipartite tracking consensus problem for high-order nonlinear Multi-Agent Systems (MASs) with cooperative–antagonistic agents interacting via a directed non-ideal communication network. For a more realistic interaction scenario, a different time-varying delay is associated to each communication link connecting a couple of agents, whose actual value is determined by the current wireless channel condition. In this context, we propose a novel distributed delayed bipartite tracking consensus control strategy which ensures the exponential stability of the whole networked control system. The theoretical analysis, carried out via Lyapunov theory and Halanay's Lemma, provides the control gains tuning rule and an estimation of the maximum admissible delay upper bound. Numerical simulations corroborate the theoretical derivations.